Semiotic Analysis of Family Communication in the Film Later, We'll Talk About Today - Rahajeng Nur Azizah Pratiwi; Ratri Kusumaningtyas (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Film is the result of current technological developments and film is also one of the media in mass communication. In a film, there must be symbols and signs hidden from every scene in it. These symbols and signs have the meaning in them. As in the film Nanti Kita Cerita Tentang Hari Ini, in this film there is a family communication that happen and contains symbols and signs in the communication. This study purpose to know the kind of family communication in the film Nanti Kita Cerita Tentang Hari Ini. The methodology used is a qualitative research with the semiotic approach of Roland Barthes. The data uses primary data from cutscenes and scenes from the film Nanti Kita Cerita Tentang Hari Ini  and secondary data from the literature to support primary data. The results of this study there are three kinds of family communication, is symbolic communication in the kind of a hand pointing gesture shows an attitude of anger, holding hands and stroking the shoulders shows a calming and embracing attitude showing the attitude that parents will always love their children. Non-verbal communication in the kind of bowing the head shows an attitude of worrying about the child's condition, supporting the chin and glaring eyes showing an angry attitude. And verbal communication.